Antioxidant and Antidiabetic Potential of Saponin Fraction Isolated from Moringa oleifera Leaves: Antioxidant Potential of Saponin Fractions (Biological Sciences - PJSIR, 2020)
To assess total phenolic contents, total flavonoid contents (TPC, TFC), DPPH scavenging and antidiabetic (antiglycation and alpha amylase hindrance) activities of Moringa oleifera (MO) leaves, bio- assay guided fractionation was used with thin layer chromatography profile to isolate saponin fraction (SF). The TPC and TFC were 9.7-12.8 GAE and 5.3-9.3 CE (g/100 g dry weight), respectively and aqueous and methanol fractions were more effective. DPPH scavenging activity ranged 69.5-83.1%. SF displayed noteworthy antioxidant ability (p